2014
DOI: 10.1002/pds.3592
|View full text |Cite
|
Sign up to set email alerts
|

Hospital admissions/visits associated with drug–drug interactions: a systematic review and meta‐analysis

Abstract: Drug-drug interactions are a significant cause of hospital admissions and hospital visits. Improved DDI information gathering could help to reduce such adverse effects from DDIs, especially for patients using non-steroidal anti-inflammatory drugs and warfarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
180
0
19

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(203 citation statements)
references
References 49 publications
4
180
0
19
Order By: Relevance
“…17 The high prevalence of observed PDDI exposures does not correspond with reported rates of ADEs, which either occur or are recognized far less frequently. 2,8,18,19 At the same time, ADEs can result in significant morbidity and mortality. [20][21][22] Our findings therefore point to a central problem or tradeoff of warning systems, encapsulated by the story of the boy who cried wolf: the current compendiums of PDDIs suffer from identifying so many PDDIs that the signal of true potential patient harm may get lost in the noise of too many alarms.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…17 The high prevalence of observed PDDI exposures does not correspond with reported rates of ADEs, which either occur or are recognized far less frequently. 2,8,18,19 At the same time, ADEs can result in significant morbidity and mortality. [20][21][22] Our findings therefore point to a central problem or tradeoff of warning systems, encapsulated by the story of the boy who cried wolf: the current compendiums of PDDIs suffer from identifying so many PDDIs that the signal of true potential patient harm may get lost in the noise of too many alarms.…”
Section: Figurementioning
confidence: 99%
“…4 The epidemiology of pediatric PDDIs, however, is largely unknown: we lack estimates of the prevalence of pediatric PDDIs, reliable knowledge regarding the risk posed by specific PDDIs (especially important given the countervailing risks posed by the condition under treatment), or an adequate understanding about pathways by which PDDIs may lead to harmful ADEs in pediatric patients (eg, as a direct physiologic effect on an organ system or through modulation of another medication's effect). [6][7][8] Each of these critical pieces of information is integral to developing and studying strategies to mitigate clinically important ADEs associated with specific PDDIs.…”
mentioning
confidence: 99%
“…A recent meta-analysis of studies found that 22.2% of adverse drug event associated hospital admissions were attributable to drug-drug interactions (interquartile range 16.6 -36.0%) [1]. Ensuring that medication therapy occurs safely and to the maximum benefit of any given patient is of great interest to clinicians [2].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of DDIs in hospitalized patients is one of the major causes of adverse events [4,5]. In ambulatory patients, DDIs represent 0.1% of hospital visits and 1.1% of hospital admissions [6], resulting in increased hospital stay days, as well as higher costs D DAVID PUBLISHING associated with healthcare [7,8]. The risk factors associated with DDIs include age, the number of prescription medications, the presence of comorbidities and the number of hospital stay days [3,[9][10][11].…”
mentioning
confidence: 99%